Propofol and Dexmedetomidine potentially maintain BIS, MAP, and BGA in Brain Tumor Patients - Ismail, Taufik Suryadi; Kulsum, Kulsum; Khairuddin, Khairuddin; Jamal, Fachrul (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2026)
Introduction: Brain tumors have a high morbidity and mortality rate in Indonesia. According to data from the Ministry of Health, in 2020 the incidence of brain tumors was around 1.5 percent of all tumor cases. Anesthesia for brain tumor removal surgery has a high risk of postoperative complications such as hypotension, bleeding and intracranial infection. Propofol and dexmedetomidine are often used as anesthetic agents in neurosurgery that affect hemodynamics, depth of anesthesia and blood gas analysis. This study aims to determine the comparative effectiveness of propofol compared to dexmedetomidine on Bispectral Index (BIS), mean arterial pressure (MAP), and blood gas analysis (BGA) in patients undergoing intracranial tumor removal surgery.Subject and Method: This study is an unpaired numerical comparative analytical observational study. A total of 42 participants who met the inclusion and exclusion criteria were randomly assigned into 2 groups, namely the propofol and dexmedetomidine groups. Furthermore, an assessment of mean arterial pressure, BIS, and BGA was carried out.Results: Based on statistical tests using the unpaired T test, it was found that intraoperative MAP was significantly different between the two groups (p0.05), where dexmedetomidine had a more stable MAP. While in BIS and BGA there was no significant difference in the two groups (p0.05) statistically using the Mann Whitney test.Conclusion: Dexmedetomidine has an effect that is not much different compared to propofol in maintaining changes in MAP, BIS and BGA in patients with intracranial tumor removal surgery.